Enantioselective Synthesis of Substituted Dihydropyrans by Organocatalyst-Mediated Domino Michael/Enolization/Acetalization Reactions - Hayashi, Yujiro; Han, Xiaolei; Hack, William R. (Synlett, 2024)
A highly enantioselective synthetic method for 3,4-trans-dihydropyrans was developed by the reaction of α-acyl-β-aryl-substituted acrylonitrile and aldehyde catalyzed by diphenylprolinol silyl ether. This is an asymmetric domino reaction via a catalytic Michael reaction/enolization/acetalization.
Keywords: dihydropyrans; asymmetric synthesis; organocatalysis; diphenylprolinol silyl ether; domino reaction; α-acyl-β-aryl-substituted acrylonitrile